Implementasi Asas Peradilan Terbuka untuk Umum pada Masa Pandemi Covid-19 terhadap Pemeriksaan Perkara Pidana di Pengadilan Negeri Donggala - Titie Yustisia Lestari; Andi Afdhaliah Sri Hayati (Departement of Mathematics Education, 2023)
The Covid-19 pandemic that has occurred in Indonesia since 2020 has had a very significant impact on the criminal justice system in Indonesia. The process of resolving criminal cases by law enforcement officers must be handled virtually. This of course has an impact on the principles that have been regulated in the Criminal Procedure Code and the Judicial Power Act, one of which is the principle of an Open Trial for the Public. The virtual trial of course imposes restrictions on the public to attend directly in the courtroom because of the government's policy to implement health protocols. This study aims to determine the implementation of the principle of open justice to the public during the Covid-19 pandemic on the examination of criminal cases at the Donggala District Court and to identify obstacles in the implementation of the principle of open justice to the public during the Covid-19 pandemic on the examination of criminal cases at the Donggala District Court. This research was conducted in Donggala Regency, namely the Donggala District Court by taking samples of Judges, Prosecutors and Heads of Detention Centers. Data was collected using interview techniques and document studies. The data were analyzed descriptively qualitatively. The results showed that the implementation of the principle of an open trial to the public during the Covid-19 pandemic for the examination of criminal cases at the Donggala District Court, namely the principle of an open trial to the public was still applied by judges in trials conducted both online and offline, although there were restrictions on participation. Public. In principle, the public can attend the trial through two channels, namely attending with restrictions directly in the courtroom by implementing health protocols and attending the trial online using the zoom link shared by the Donggala District Court via social media.